2014
DOI: 10.1002/2014ja020183
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of seasonal and longitudinal variability of EEJ in the Indian region

Abstract: This paper presents the seasonal and longitudinal variability of the equatorial electrojet (EEJ) based on geomagnetic variation data from two electrojet stations in the northern Indian Ocean at a longitudinal separation of~15°: i.e., at 77°E and at 93°E. One complete year of data is used (i.e., from November 2011 to October 2012) at the two longitudes and compared with the climatological model of the equatorial electrojet (EEJM-2.0). The results of our analysis show that (i) the monthly averaged hourly values … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
24
1

Year Published

2015
2015
2018
2018

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 17 publications
(35 citation statements)
references
References 52 publications
7
24
1
Order By: Relevance
“…It has been established earlier that the eastward electric field ( E region) at equator shows a four‐wave longitudinal structure with a crest at 100°E and a trough at 60°E longitude, attributed to DE3 nonmigrating tide (Lühr et al, ). Similar trend was noted in comparison of CBY and VEN and EEJ and CEJ strengths (Chandrasekhar et al, , , )(from 93–77°). Additionally, using a year's concurrent data with MNC (72°), the westward decrease in EEJ strength as well as increase strength of westward currents demonstrated in a separate analysis (Archana R. K., personal communication, June 25, 2018).…”
Section: Discussionsupporting
confidence: 85%
“…It has been established earlier that the eastward electric field ( E region) at equator shows a four‐wave longitudinal structure with a crest at 100°E and a trough at 60°E longitude, attributed to DE3 nonmigrating tide (Lühr et al, ). Similar trend was noted in comparison of CBY and VEN and EEJ and CEJ strengths (Chandrasekhar et al, , , )(from 93–77°). Additionally, using a year's concurrent data with MNC (72°), the westward decrease in EEJ strength as well as increase strength of westward currents demonstrated in a separate analysis (Archana R. K., personal communication, June 25, 2018).…”
Section: Discussionsupporting
confidence: 85%
“…[], Doumouya and Cohen [], and Chandrasekhar et al . [] when there is no influence due to SSW. Doumouya et al .…”
Section: Resultsmentioning
confidence: 99%
“…Chandrasekhar et al . [] showed that EEJ current is strongest in South America sector (western axis) and weakest in India sector (eastern axis). In the worldwide context summary, magnetic field variations are stronger in the western than the eastern axis.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Numerical and observational studies of the variability of ionospheric features in the middle and low latitudes have been conducted over the years; however, there are limited studies focused exclusively on longitudinal variability due to the univeral time (UT) onset time in the low latitudes. Explorations of the longitude sector differences of equatorial spread F have been conducted by several groups[ Aarons , ; Fejer et al , ; Abdu et al , ; Oladipo et al , ], and several studies have found an impact of longitudinal effects on the equatorial electroject (EEJ) [ England et al , ; Klimenko and Klimenko , ; Yizengaw et al , ; Phani Chandrasekhar et al , ]. It has also been recognized that the neutral atmosphere plays a critical role through nonmigrating tidal influences [ Immel et al , ; Forbes et al , ; Maute et al , ] and longitudinally dependent thermospheric winds [ Fuller‐Rowell et al , ; Sojka et al , ] in the distribution of plasma.…”
Section: Introductionmentioning
confidence: 99%